Inspection Scheduling Programs Analysis of Amine Reboiler Heat Exchanger Using Risk-Based Inspection API 581 Method - Khoirunnisa Mahdiyah Syawalina; Dwi Priyanta; Nurhadi Siswantoro (International Journal of Marine Engineering Innovation and Research, 2020)
In the oil and gas industry, the purification and handling of oil and petroleum gas, the cycle of warmth transformation is expected to isolate the H2S and CO2 from natural gas with an amine. The cycle happens inside the amine reboiler which is a shell and tube heat exchanger type. Cycle liquid streaming in the Amine Reboiler are Lean Amine on the shell side (HEXSS) and Therminol-55 on the cylinder/tube side (HEXTS). With such synthetic arrangement, worked with high weight and temperature, makes the liquid into a destructive climate for Amine Reboiler. Along these lines, an exact review and planning program is needed to guarantee equipement’s life, guaranteeing the protected establishment and wellbeing of laborers. Thus, it is important to direct a danger assessment for shell and tube heat exchanger gear utilizing the Risk-Based Inspection technique which alludes to the API RP 581. The danger of Amine Reboiler is a mix of the Probability of Failure (PoF) and the Consequence of Failure (CoF). From the PoF and CoF acquired, the HEXSS hazard level on the danger lattice at the RBI date and RBI plan date are ordered as Low Risk and Medium Risk. While the danger level of HEXTS on danger network at RBI date and RBI plan date both are ordered as Medium-High Risk. At that point the prescribed date to do the assessment is January 1, 2020.